LINGUISTIC GLOBALIZATION AND PROBLEMS OF LANGUAGE DIVERSITY - Mukhlisa Odilova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article analyzes the process of linguistic globalization and its impact on language diversity. The development of global communication and technology strengthens the dominance of certain languages, while minority languages face the risk of disappearance. The study also discusses possible ways of preserving linguistic diversity.